The Potential of Protection System of Curator and Administrator Profession in Indonesia (Comparative Analysis of Curator and Notary Profession in Indonesia) - Ghassani Yudistira, Banat Aghniya (UI Scholars Hub, 2025)
This thesis explores the potential need for a protection system for curators and administrators in Indonesia’s bankruptcy proceedings, highlighting their vulnerability to criminalization despite fulfilling roles mandated by law. The study begins by outlining the duties and responsibilities of curators and administrator under Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations (UU KPKPU), emphasizing their legal obligation to manage and settle bankrupt assets independently and without conflict of interest. However in practice, curators and administrators often face legal threats and being criminalized, including police reports and criminal charges, merely for executing duties outlined in the statute. In contrast, legal professions such as notaries enjoy procedural protections through the Notary Supervisory Council, as regulated in Law No. 2 of 2014 on the Notary Office. This research employs a normative legal method, comparing statutory provisions and analyzing real-world cases of curator criminalization. By drawing comparisons with the notary profession, the thesis argues for the institutionalization of similar protection mechanisms for curators and administrators. The goal is to reduce legal uncertainty and ensure these professionals can perform their duties effectively without fear of personal legal repercussions. Ultimately, the study recommends the integration of supervisory bodies and procedural safeguards into the existing bankruptcy law framework to uphold fairness and legal protection.